Heart rate reduction for 36 months with ivabradine reduces left ventricular mass in cardiac allograft recipients: a long-term follow-up study - Dösch, Andreas; Mueller, Susanne; Gleißner, Christian A.; Frankenstein, Lutz; Hardt, Stefan; Ruhparwar, Arjang; Ehlermann, Philipp; Dengler, Thomas; Katus, Hugo; Erbel, Christian (Drug design, development and therapy, 2013)
Background: Due to graft denervation, sinus tachycardia is a common problem after heart transplantation, underlining the importance of heart rate control without peripheral effects. However, long-term data regarding the effects of ivabradine, a novel If channel antagonist, are limited in patients after heart transplantation. - Methods: In this follow-up analysis, the resting heart rate, left ventricular mass indexed to body surface area (LVMI), tolerability, and safety of ivabradine therapy were evaluated at baseline and after 36 months in 30 heart transplant recipients with symptomatic sinus tachycardia versus a matched control group. - Results: During the study period, ivabradine medication was stopped in three patients (10% of total). Further analysis was based on 27 patients with 36 months of drug intake. The mean patient age was 53.3±11.3 years and mean time after heart transplantation was 5.0±4.8 years. After 36 months, the mean ivabradine dose was 12.0±3.4 mg/day. Resting heart rate was reduced from 91.0±10.7 beats per minute before initiation of ivabradine therapy (ie, baseline) to 81.2±9.8 beats per minute at follow-up (P=0.0006). After 36 months of ivabradine therapy, a statistically significant reduction of LVMI was observed (104.3±22.7 g at baseline versus 93.4±18.4 g at follow-up, P=0.002). Hematologic, renal, and liver function parameters remained stable during ivabradine therapy. Except for a lower mycophenolate mofetil dose at follow-up (P=0.02), no statistically significant changes in immunosuppressive drug dosage or blood levels were detected. No phosphenes were observed during 36 months of ivabradine intake despite active inquiry. - Conclusion: In line with previously published 12-month data, heart rate reduction with ivabradine remained effective and safe in chronic stable patients after heart transplantation, and also during 36-month long-term follow-up. Further, a significant reduction of LVMI was observed only during ivabradine therapy. Therefore, ivabradine may have a sustained long-term beneficial effect with regard to left ventricular remodeling in heart transplant patients.
Gesehen am 17.12.2020